Peripheral vascular thrombosis in the gestational Period (Research, Society and Development, 2020)
Peripheral Vascular Thrombosis (DVT) is a disease characterized by the development of thrombi in peripheral vessels, specifically in the lower limbs. Categorize the main risk factors that lead to the emergence of Peripheral Vascular Thrombosis in pregnancy and indicate prophylactic measures for the possible complications of this disease. Qualitative research, exploratory and explanatory, with integrative guidance, through the search for scientific articles in the NCBI, PUBMED and SCIELO databases. Analyzing the extrinsic and intrinsic factors, diabetes mellitus interacts with some mechanisms linked to hemostasis; obesity is an extrinsic factor extremely linked to the development of thrombosis during pregnancy; contraceptives are drugs that increase the likelihood of developing thrombi in the vessels; deficiency of antithrombin I, favors thrombotic events both during pregnancy and in the puerperium. Prophylactic measures such as low molecular weight heparin (LMWH), a drug that interacts with antithrombin by increasing its activity, and compression stockings, act by decreasing venous stasis. Vascular thrombosis during pregnancy is entirely linked to intrinsic factors in conjunction with extrinsic factors. LMWH is a preferable medication during this period, as well as compression stockings.